A Novel Rat Model of Type 2 Diabetes: The Zucker Fatty Diabetes Mellitus ZFDM Rat. (26th February 2013) - Yokoi, Norihide; Hoshino, Masayuki; Hidaka, Shihomi; Yoshida, Eri; Beppu, Masayuki; Hoshikawa, Ritsuko; Sudo, Katsuko; Kawada, Akihiko; Takagi, Sadaaki; Seino, Susumu
Abstract : The Zucker fatty (ZF) rat harboring a missense mutation ( fatty, fa ) in the leptin receptor gene ( Lepr ) develops obesity without diabetes; Zucker diabetic fatty (ZDF) rats derived from the ZF strain exhibit obesity with diabetes and are widely used for research on type 2 diabetes (T2D). Here we establish a novel diabetic strain derived from normoglycemic ZF rats. In our ZF rat colony, we incidentally found fa/fa homozygous male rats having reproductive ability, which is generally absent in these animals. During maintenance of this strain by mating fa/fa males and fa/+ heterozygous females, we further identified fa/fa male rats exhibiting diabetes. We then performed selective breeding using the fa/fa male rats that exhibited relatively high blood glucose levels at 10 weeks of age, resulting in establishment of a diabetic strain that we designated Hos:ZFDM- Lepr fa (ZFDM). These fa/fa male rats developed diabetes as early as 10 weeks of age, reaching 100% incidence by 21 weeks of age, while none of the fa/+ male rats developed diabetes. The phenotypic characteristics of this diabetic strain are distinct from those of normoglycemic ZF rats. ZFDM rat strain having high reproductive efficiency should serve as a more useful animal model of T2D.